IMPLEMENTASI TEAMS GAMES TOURNAMENT MODEL MENINGKATKAN MOTIVASI BELAJAR SISWA DI SD ST. ANTONIUS BANGUN MULIA MEDAN - Pasaribu, Sandiolan Alexsius; Sihotang, Din Oloan (STIPAS Keuskupan Agung Kupang, 2024)
This study investigates the effectiveness of implementing the Teams Games Tournament (TGT) model in enhancing students' motivation in the subject of Catholic Education for Grade V B at SD St. Antonius Bangun Mulia Medan during the academic year 2023/2024. The research adopts an action research approach with two cycles, where the first cycle showed students' motivation levels at a